Evaluation of the genotoxicity of zinc oxide-eugenol cement to Allium cepa L. - doi: 10.4025/actascibiolsci.v35i4.17925 (Acta Scientiarum. Biological Sciences, 2013)
Evaluation of the Genotoxicity of Zinc Oxide-Eugenol Cement in Allium cepa L. Dental materials can induce local and systemic effects. The Allium cepa assay was used to evaluate the genotoxicity and/or cytotoxicity of zinc oxide and eugenol (ZOE) at different proportions. The ZOE solution was tested at the concentration of 1 drop of eugenol (in each drop of liquid, the approximate concentration of eugenol is 85%) and 1 portion of zinc oxide cement (treatment I), and twice the concentration of eugenol (treatment II). Treated roots appeared to be yellowish-brown, fewer in number, thicker and less turgid compared with the control, suggesting a cytotoxic activity of ZOE. A significant difference was found in the root size between the control and treatment II. This treatment reduced by 79% the size of the root compared with the control, and the mitotic index was 66%, indicating a 22.4% reduction relative to the control, which in turn evidenced the cytotoxicity of ZOE. The significant increase in anaphase bridges suggests a genotoxic effect.